Endophytic Fungi Associated with Cinnamomum iners Leaves in UNIMAS, Malaysia - Yap, Shoo Yuen (Universiti Malaysia Sarawak (UNIMAS), 2015)
Endophytic fungi are fungi that colonize within living plant tissues without causing any symptoms of disease, but they might provide a novel, alternative and eco-friendly compound. The present study was to observe the diversity, distribution and community structure of endophytic fungi of Cinnamomum iners in UNIMAS, Malaysia. The leaf segments were immersed in 75% ethanol for about one minute, in 65% Clorox for ten minutes, in 75% ethanol about 30 seconds and washed in sterilized distilled water for three times before plated on water agar and obtained their pure culture. A total of 287 isolates belonging to 14 species of endophytic fungi were isolated from 75 segments of young, mature and senescence leaves of C. iners. The percentage of occurrence of the fungi on senescence leaf (112 isolates with 39.02%) was higher than on mature (94 isolates with 32.75%) and young leaves (81 isolates with 28.22%). Of these 14 species, seven species, 12 species and nine species were isolated from young, mature and senescence leaf segments of C. iners, respectively. The percentage of occurrence of endophytic fungi isolated from young leaves was more in November, mature leaves in December and senescence leaves in October as compared to other sampling months. Species 3, Penicillium sp., Colletotrichum sp.2 and Colletotrichum sp.3 occurred in all the three leaf maturity stages of C. iners. Species 3 was the most abundant endophytic fungi in the senescence leaf of C. iners. Colletotrichum sp.3 occurred in all the three stages of leaf maturity but occurs at low percentages. Aspergillus aculeatus, Penicillium rolfsii and Talaromyces aculeatus were identified by PCR and DNA sequencing of ITS 4 and ITS 5. The optimum pH for fungus species growth was tends to be in slightly acidic condition. All the fungi were growing well when under incubation temperature range of 20˚C to 30˚C. The light and dark conditions did not influence much on the growth of fungi except of Aspergillus aculeatus and Species 4.